The Effect of Soil Type and Ecosystems on the Soil Nematode and Microbial Communities - Renčo, M. (Helminthologia, 2020)
Integrated studies are required to better understand the relationships between groups of soil microfauna under the influence of various biotic and abiotic factors that drive and characterise ecosystems. We analysed soil nematode communities and microbial diversity and the properties of three soil types to assess the effect of these environmental variables on biological diversity in natural (forest), semi-natural (meadow), and managed (agriculture) habitats of the Slovak Republic. The type of ecosystem and soil and the interaction of both factors had considerable effects on most monitored abiotic and biotic soil properties. The forest with a Chernozem soil had the most nematode species, highest nematode diversity, highest abundance of nematode within functional guilds, best values of ecological and functional indices, highest microbial biomass, highest microbial richness and diversity, and the highest values of various soil properties, followed by meadows with a Cambisol soil. The agricultural ecosystem with a Stagnosol soil had the lowest biological diversity and values of the soil properties. Several nematode species were new for Slovak nematode fauna. Sampling date and the interaction of all three factors (ecosystem × soil × date) had minor or no effect on most of the parameters, except soil moisture content, microbial richness, nematode channel ratio, nematode maturity index, and plant parasitic index. Both the biological indicators and basic soil properties indicated that the natural forest with a Chernozem soil was the best habitat from an ecological point of view. This ecosystem is thus the most appropriate for ecological studies.